M.G. Vassanji‟s The Book of Secrets: A Postmodern Study - S.A., AHILWIN.; Prasad Pandey, SANJAY (International Journal of Psychosocial Rehabilitation, 2021)
Vassanji is double the champ of the Giller Prize for his novel, The Book of Secrets in the year 1994. History plays a major role in the novel. Discovering the facts is not an easy thing. He portrays how history is to be presented or reproduced though the characters’ personalities. The novel consists of letters, journals, diary. Stream of consciousness is the narrative technique used in this novel. Quest of identity is one of the main themes. The first person narrated the whole story. Superstitious beliefs prevail in the shamsi community people is described. Postmodernism plays a major role in the novel. The elements of postmodernism such as Minimalism, Maximalism, Magic Realism, fragmentation, Pastiche, Skepticism were found in the novel. This present paper is an attempt to explore the postmodern elements in M.G. Vassanji’sThe Book of Secrets.